The promise - Davies, Nicola 1958- (Candlewick Press, 2017)
On a mean street in a mean, broken city, a young girl tries to snatch an old woman's bag. But the frail old woman, holding on with the strength of heroes, says the thief can't have it without giving something in return: the promise. It is the beginning of a journey that will change the thieving girl's life--and a chance to change the world, for good
"Ages 5-9"
Keywords: Promises / Juvenile fiction; Acorns / Juvenile fiction; Theft / Juvenile fiction; Picture books for children; Promesses / Romans, nouvelles, etc. pour la jeunesse; Glands / Romans, nouvelles, etc. pour la jeunesse; Vol (Droit) / Romans, nouvelles, etc. pour la jeunesse; Livres d'images pour enfants; Acorns; Promises; Theft; Picture books; Fiction; Juvenile works